2020
DOI: 10.1111/jch.13785
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure variability at different time periods within first 24 hours after admission and outcomes of acute ischemic stroke

Abstract: This study discusses the association between blood pressure (BP) variability at different time periods within first 24 hours after admission and the functional outcome in acute ischemic stroke (AIS). We observed BP variability within first 24 hours after admission and evaluated the association between BP variability at different time periods (4 am‐8 am, 10 am‐2 pm, 4 pm‐8 pm, 10 pm‐2 am) and the functional outcome in AIS. National Institute of Health Stroke Scale (NIHSS) and modified Rankin Scale (mRS) were ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Studies on the short-term influence of DBP variability on the neurological outcomes of patients with AIS are inconsistent. Our results are in line with studies that uncovered that DBP variability contributes to the functional deterioration of patients with AIS [20][21][22][23], although the majority of the literature exhibit that SBP variability is a better predictor of worse neurological outcomes [11,14,15,24,25]. While a high DBP variability may impact the ventricular end-diastolic volume and the cerebral perfusion in patients with impaired cerebral blood flow autoregulation, the J-curve relationship between DBP and cardiovascular events may produce a confounding effect on stroke outcomes [26].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Studies on the short-term influence of DBP variability on the neurological outcomes of patients with AIS are inconsistent. Our results are in line with studies that uncovered that DBP variability contributes to the functional deterioration of patients with AIS [20][21][22][23], although the majority of the literature exhibit that SBP variability is a better predictor of worse neurological outcomes [11,14,15,24,25]. While a high DBP variability may impact the ventricular end-diastolic volume and the cerebral perfusion in patients with impaired cerebral blood flow autoregulation, the J-curve relationship between DBP and cardiovascular events may produce a confounding effect on stroke outcomes [26].…”
Section: Discussionsupporting
confidence: 89%
“…To our knowledge, this is the first study to evaluate BPV in patients with AIS beyond 24 hours after admission and its relationship with outcomes at discharge. Furthermore, we analyzed BPV as a continuous variable at different time intervals, whereas previous studies considered its cumulative effect by dividing patients into percentiles according to their blood pressure indices [10,11,14,29]. This approach may result in the loss of statistical power, and using a continuous covariate provides a better understanding of the impact of minute and gradual changes in BPV on the functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different factors have been associated with the outcome stroke such as oxidation [17,18], inflammation [19][20][21][22], hyperglycemia [23], or alterations in brain perfusion due to blood pressure variability [24,25]. In addition, there has been found the association of RDW with oxidative stress in animal models [26], with blood TNF-alpha levels in critically ill patients [27,28], and with atrial fibrillation and its risk of complications and mortality [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Different views exist on antihypertensive therapy for acute ischemic injury, and this presents a challenge to the management of BP in PRES. Meanwhile, in the acute phase of cerebral ischemic injury, severe fluctuations of BP should be avoided; Geng et al (39) found that severe fluctuation of SBP within 24 h of onset was an independent risk factor for poor prognosis at 7 days. Manning et al (40) also proved that fluctuations of SBP within 24 h of infarction was an independent risk factor for hemorrhagic transformation.…”
Section: Management Of Bp In Acute Cerebral Infarctionmentioning
confidence: 99%